C5a inhibitor protects ischemia/reperfusion injury in rat small intestine - Tuboly Eszter; Futakuchi Mitsuru; Varga Gabriella; Érces Dániel; Tőkés Tünde; Mészáros András; Kaszaki József; Suzuiki Masumi; Imai Masaki; Okada Alan; Okada Noriko; Boros Mihály; et al. (2016)
Acute mesenteric ischemia (AMI) is caused by considerable injury in the intestine, which is associated with intestinal ischemia followed by reperfusion (Treat-I/R). To elucidate the mechanisms of I/R injury, we examined role of C5a anaphylatoxin using a C5a inhibitory peptide termed AcPepA, induction of inflammatory cells, and cell proliferation of the intestinal epithelial cells in the experimental AMI model. Rats were exposed to occlusion of the superior mesenteric artery and subsequent reperfusion. Other groups were treated with AcPepA before ischemia or reperfusion. Treat-I/R induced injuries in the intestine, and AcPepA significantly reduced the proportion of severely injured villi. Treat-I/R induced C5L2 (secondary receptor for C5a)-positive polymorphonuclear leukocytes in the vessels and CD204-positive macrophages (CD204 + MACs) near the injured site, which was correlated with hypoxia induced factor 1-alpha (HIF1-alpha)-positive cells. Induction of these inflammatory cells was attenuated by AcPepA. In addition, AcPepA increased the proliferation of epithelial cells in the villi, possibly preventing further damage which then proliferated in recovery from the stress. Therefore, Treat-I/R activated C5a followed by the accumulation of PMN and HIF-1alpha-producing macrophages, leading villus injury. AcPepA, C5a inhibitory peptide, blocked the deleterious effects of C5a, indicating therapeutic effect on inflammatory consequences of experimental AMI.